Temuan Gerabah di Pura Wasan, Blahbatuh, Gianyar (Suatu Pendekatan Etnoarkeologis) - I Wayan Badra (Balai Arkeologi Sumatera Utara, 2017)
AbstractWasan is the name of a subak (Balinese traditional irrigation system) that is located eastern of Banjar Blahtanah and around Banjar Canggi (banjar = community unit). Wasan yielded a number of archaeological finds such as candi (temple), pond, building structure, figurine, animal statues, lingga, yoni, and potsherds. The purpose of this research is to find out the shapes and functions of the potsherds which found at the temple. Data were collected by means of survey and excavation, then have been analyze for morphologically, technologically, and contextually. Results of this research include three penyembeans, three coblongs, and a jar. Derived from their shapes, the three types of pottery have different functions. Penyembean was functioned as a container to ignite fire before the commencing of a yadnya ceremony at Pura Wasan. Coblong was used to place holy water or (tirtha), while the jar, due to its larger size, besides being functioned to store tirtha, could also be used as a container for toyeanyar during religious ceremonies. AbstrakWasan merupakan nama sebuah subak yang terletak di sebelah timur Banjar Blahtanah dan di sekitar Banjar Canggi. Wasan mengandung beberapa tinggalan arkeologis di antaranya candi, kolam, struktur bangunan, arca perwujudan, arca binatang, lingga yoni, dan sejumlah fragmen gerabah. Adapun tujuan penelitian ini adalah untuk mengetahui bentuk dan fungsi temuan gerabah yang terdapat di pura tersebut. Data penelitian ini dikumpulkan melalui survei dan ekskavasi, kemudian dianalisis secara morfologi, teknologi, dan kontekstual. Hasil penelitian ini berupa tiga buah penyembean, tiga buah coblong, dan sebuah periuk. Berdasarkan ketiga bentuk gerabah ini mempunyai tiga fungsi yang berbeda-beda. Penyembean dapat difungsikan sebagai wadah tempat menyalakan api ketika upacara yadnya di Pura Wasan dimulai. Coblong dapat difungsikan sebagai wadah tempat air suci atau tirtha, sedangkan periuk yang bentuknya lebih besar, selain difungsikan sebagai tempat tirtha dapat juga dipakai sebagai wadah tempat toye anyar dalam pelaksanaan upacara agama.